Design issues in distributed software - Maurya A.K.; Tripathi D.; Biswas A.; Tripathi A.K. (My University, 2025)
With the advent of fast advancing microprocessor technology, software designers and users in various fields tend to use distributed software to solve realworld problems. The researchers already worked on the issues regarding the distributed systems. Now, in this work, we identify and address the design issues underlying distributed software. Before this, we give the motivation behind the development of distributed software and describe the objectives that should be addressed when dealt with the issues of distributed software. Further, we carefully analyze and locate constraints related to identified issues, that become associated challenges in the context of the objectives governing the distribution idea. © 2018 IEEE.